PENGARUH PENGAMBILAN TRAINING SAMPLE SUBSTRAT DASAR BERBEDA PADA KOREKSI KOLOM AIR MENGGUNAKAN DATA PENGINDERAAN JAUH - Budhiman, Syarif; Winarso, Gathot; Asriningrum, Wikanti (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2013)
Lyzen ga (1978, 1981) developed a method to correct the water column using a ratio of bottom waters substrates reflectance on 2 (two) different bands, assuming that the ratio is the same for a different bottom type. The problem arise when the Lyzenga method was being simplified. In this case by sampling different bottom substrates as input. This study aims to compare the effects of the simplification process with the result of the calculation using the actual Lyzenga method. The calculation of water column correction followed the process described in the guide by UNESCO (1999) and Green et al (2000). The results showed that samples from two different substrates which has a very different radiance (reflectance) increased the index value of the substrate in deeper water.